2007
DOI: 10.4141/p05-192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed treatments on emergence, yield, and root rot severity of soybean under Rhizoctonia solani inoculated field conditions in Ontario

Abstract: . 2007. Effect of seed treatments on emergence, yield, and root rot severity of soybean under Rhizoctonia solani inoculated field conditions in Ontario. Can. J. Plant Sci. 87: 167-173. Field trials were conducted with soybean at two sites each year from 2001 to 2003 in Ottawa, ON, to determine the effect of seed treatments with various combinations of seven formulated fungicides and the bioagent Yield Shield (Bacillus pumilus GB34) under Rhizoctonia solani inoculated conditions. Controls were untreated seed pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…All Fusarium isolates were identified to species based on the morphological characteristics described by Nelson et al (1983). Inoculum of the different species was prepared separately using the wheat kernel technique as previously described (Xue et al 2006) with minor modifications. One kilogram of wheat kernels was soaked in tap water for 24 h, and then autoclaved at 1218C and a pressure of 1.05 kg cm (2 for 60 min.…”
Section: Materials and Methods Production Of Fusarium Inoculamentioning
confidence: 99%
See 1 more Smart Citation
“…All Fusarium isolates were identified to species based on the morphological characteristics described by Nelson et al (1983). Inoculum of the different species was prepared separately using the wheat kernel technique as previously described (Xue et al 2006) with minor modifications. One kilogram of wheat kernels was soaked in tap water for 24 h, and then autoclaved at 1218C and a pressure of 1.05 kg cm (2 for 60 min.…”
Section: Materials and Methods Production Of Fusarium Inoculamentioning
confidence: 99%
“…Plant height was measured from the cotyledons to the top of the meristem. Root rot severity was rated on a 0Á5 scale as previously described (Xue et al 2006) where: 0 0no disease; 1 0slight necrosis or a few lesions on roots with total diseased area 0 to05%; 2 0slight to moderate necrosis or lesions on roots with total diseased area 5 to010%; 3 0moderate necrosis or lesions with total diseased area 10 to 025%; 4 0extensive necrosis or lesions on roots with total diseased area 25 to 050%, and seedling growth is hampered; and 50extensive necrosis or lesions on roots with total diseased area 050%, and seedling growth is seriously hampered or leading to death. To determine root dry weight, roots were cut off at the soil line, dried at 658C for 5 d, and subsequently weighed.…”
Section: Plant Inoculationmentioning
confidence: 99%
“…These BCAs are natural soil inhabitants and once established in the rhizosphere, these are able to suppress the pathogen by active antagonism, mainly antibiosis and competition (Chet, 1989 andFravel et al, 1985) and also enhance plant growth by production of volatiles (Chang et al, 1986). Of the different methods of application of fungicides and biocontrol agents, seed treatments have been most favoured and used, and there are several studies to show that the BCAs applied on seed established in the rhizosphere and provide good suppression of the pathogens and diseases (De and Mukhopadhyay, 1990;Vyas, 2001 andXue et al, 2007). The used of BCAs as seed treatment results in their easily establishment in the developing rhizosphere, causing a "preempt" effect, where the established BCAs are able to suppress the activities of the pathogens through active antagonism (competition, exploitation and antibiosis).…”
Section: Evaluation Of Promising Fungicides Biocontrol Agents and Bomentioning
confidence: 99%
“…Frank) Donk) causes seedling blight, including pre-and post-emergence damping-off and root rot of young and adult soybean plants. (Xue et al 2007;Zhang et al 2013;Chang et al 2015b;McLaren et al 2015). In the United States, rhizoctonia root and hypocotyl rot causes damping-off as well as lesions on hypocotyls and roots of soybean (Wrather 2001).…”
mentioning
confidence: 99%
“…An earlier study concluded that most ancestral soybean lines and commercial soybean cultivars in the United States were susceptible to R. solani, while some showed partial resistance (Bradley et al 2001). In eastern Canada, cultivar resistance to rhizoctonia root rot is not available and disease management is largely dependent on the use of fungicide seed treatments (Xue et al 2007). Based on the root rot severity on 70 soybean cultivars evaluated for field resistance, only three were resistant to R. solani (Zhang et al 2013).…”
mentioning
confidence: 99%